Ramification of post-harvest thermal disinfestation technology for mango fruit flies [Bactrocera spp. (Diptera: Tephritidae)] across India (Current Horticulture, 2024)
Mango (Mangifera indica) is the most  important fruit crop of India with high  potential in export and foreign exchange.  An impediment in mango fruits export has been  the infestation by Bactrocera dorsalis (Hendel) and  B. zonata (Saunders). The adoption of pre-harvest  Integrated Pest Management (IPM) developed by  ICAR-Indian Institute of Horticultural Research  (IIHR) reduced infestation by 95% (Stonehouse et al.,  2005, Verghese et al., 2002). Subsequent improvement  of pre-harvest control using ovipositional deterrence  gave more than 98% control (Verghese et al., 2020).  However, for exports, 100% disinfestation is mandatory.  For the most part, postharvest pest control is focused  on trade and exports. In order to achieve safe post harvest disinfestation several experiments and studies  were conducted on main commercial varieties using  hot water (45oC to 48oC), for different lengths of time to  standardize the thermal disinfestation protocol which  is internationally acceptable (Yahia and Campos, 20.  All the studies were conducted at ICAR-IIHR where  orchards of major export mango varieties are available.
Keywords: thermostat; post-harvest; laboratory